Ionic polymer gelator, preparation method and application thereof, and gel lubricant

By adding ionic polymer gel factor to the lubricant, the problem of thin adsorption film during the friction process of low molecular weight gel lubricants is solved, which significantly improves the tribological properties and mechanical stability.

CN119505068AActive Publication Date: 2025-02-25LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411726437.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The adsorption film formed by existing low molecular weight gel lubricants during friction is thin, resulting in poor mechanical stability and insufficient tribological properties.

Method used

The ionic polymer gel factor is used as the lubricant additive and prepared by radical polymerization, including units and polar ions with a specific mole ratio to improve the tribological properties of the gel.

Benefits of technology

It significantly improves the tribological properties of gel lubricants, forms a thicker adsorption film, reduces friction coefficient and wear, and improves mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505068A_ABST
    Figure CN119505068A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lubricants, in particular to an ionic polymer gelator, a preparation method and application thereof and a gel lubricant. The ionic polymer gelator provided by the invention has good solubility in mineral base oil, synthetic base oil and other base lubricating oil; besides, the ionic polymer gelator contains N, O, S and P heteroatoms, the elements and the metal surface form a strong adsorption layer through polar parts of the elements, good lubricity is provided, direct contact of the metal surface is reduced, the elements and the metal surface are subjected to a friction chemical reaction in the friction process, a layer of friction chemical reaction film is generated, and the friction effect is improved. And metal is protected from mechanical wear and chemical corrosion. The ionic polymer gelator provided by the invention is added into base oil as a lubricating oil additive, shows good tribological performance, not only solves the problem of poor oil solubility of ionic liquid, but also improves the tribological performance of polymer gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricants, and in particular to an ionic polymer gel factor and a preparation method and application thereof, and a gel lubricant. Background Art

[0002] In recent years, gels have been widely used in lubricants and have attracted increasing attention due to their excellent lubrication properties, relatively high thermal stability, and adjustable controllability. Compared with traditional lubricants, gel lubricants not only form a three-dimensional network structure through the self-assembly of gelling agents, solving the problems of lubricant leakage and volatilization, but also have good fluidity and thermal conductivity when heated or sheared.

[0003] Low molecular weight (LMW) gel lubricants have been well studied and show excellent anti-wear performance, anti-slip ability, heat dissipation, shear thinning and creep recovery properties. Although LMW gels have shown significant advantages in these studies, their viscosity and mechanical strength are still low due to the short molecular chain of the gel. In addition, given that the lubrication quality of the contact surface is closely related to the thickness and distribution of the surface adsorption film, the relatively thin adsorption film formed by LMW gels during friction needs to be further enhanced.

[0004] Compared with traditional LMW gels, polymer gels have higher molecular weights, more complex, unique and controllable molecular structures, and are therefore better able to maintain their shape and function under pressure. In addition, polymer gels offer a wide range of customization options for the structure, which makes it easier for them to meet lubricant requirements under different operating conditions through molecular design and precise control of gel properties. Therefore, polymer gels are expected to solve the problems of poor mechanical stability and thin adsorption films associated with LMW gels. However, the tribological properties of polymer gels need to be improved.

[0005] Ionic liquids (ILs) are widely used as pure lubricants or lubricant additives due to their unique physicochemical properties, such as viscosity-temperature characteristics, good thermal stability, and adjustable cations and anions. Compared with traditional oil-based lubricants, ILs have stronger polarity, which gives them excellent surface adsorption ability and can form stable adsorption films on friction surfaces such as metals, avoiding direct metal-metal contact at the interface, thereby reducing friction coefficient and wear. However, many ionic liquids are not oil-soluble, which limits their application in lubricating oils. Summary of the invention

[0006] The purpose of the present invention is to provide an ionic polymer gel factor and its preparation method and application, and a gel lubricant. The ionic polymer gel factor provided by the present invention is added to the base oil as a lubricating oil additive, exhibiting good tribological properties, which not only solves the problem of poor oil solubility of ionic liquids, but also improves the tribological properties of polymer gels.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides an ionic polymer gel factor having a structure shown in Formula 1:

[0009]

[0010] In formula 1, m, n and o are the molar proportions of the corresponding units, wherein m accounts for 10 to 30%, n accounts for 50 to 70%, and o accounts for 10 to 30%;

[0011] X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

[0012] Preferably, the sulfonate group comprises

[0013] Preferably, the phosphate group comprises

[0014] Preferably, m accounts for 20%, n accounts for 60%, and o accounts for 20%.

[0015] The present invention provides a method for preparing the ionic polymer gel factor described in the above scheme, comprising the following steps:

[0016] Mixing raw monomers, polar organic solvents and initiators to carry out free radical polymerization to obtain the ionic polymer gel factor;

[0017] The raw material monomers include urea monomers, octadecyl methacrylate monomers and ionic monomers, and the molar proportions of the urea monomers, octadecyl methacrylate monomers and ionic monomers in the raw material monomers correspond to the proportions of m, n and o in the gel factor of the ionic polymer respectively;

[0018] The structure of the urea monomer is shown in Formula 2, and the structure of the ionic monomer is shown in Formula 3:

[0019]

[0020] In formula 3, X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

[0021] Preferably, the temperature of the free radical polymerization reaction is 40 to 120° C., and the time is 4 to 12 hours.

[0022] Preferably, the mass of the initiator is 0.5-2% of the mass of the raw monomer.

[0023] The present invention provides the use of the ionic polymer gel factor described in the above scheme or the ionic polymer gel factor prepared by the preparation method described in the above scheme as a lubricating oil additive.

[0024] The present invention provides a gel lubricant, comprising a base lubricating oil and an ionic polymer gel factor; the ionic polymer gel factor is the ionic polymer gel factor described in the above scheme or the ionic polymer gel factor prepared by the preparation method described in the above scheme.

[0025] Preferably, the content of the ionic polymer gel factor in the gel lubricant is 1 to 15 wt.%.

[0026] The present invention provides an ionic polymer gel factor having a structure shown in Formula 1:

[0027]

[0028] In Formula 1, m, n and o are the molar proportions of the corresponding units, wherein m accounts for 10 to 30%, n accounts for 50 to 70%, and o accounts for 10 to 30%; X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

[0029] The ionic polymer gel factor provided by the present invention has good solubility in base lubricants such as mineral base oil and synthetic base oil; in addition, the ionic polymer gel factor contains N, O, S and P heteroatoms, which form a strong adsorption layer with the metal surface through their polar parts, provide good lubricity and reduce direct contact with the metal surface, and undergo tribochemical reaction with the metal surface during friction to generate a tribochemical reaction film to protect the metal from mechanical wear and chemical corrosion.

[0030] The present invention provides a method for preparing the ionic polymer gel factor, which is prepared by free radical polymerization. The preparation method has the advantages of simple synthesis route, low production cost, simple post-processing, etc.

[0031] The present invention provides a gel lubricant that exhibits excellent shear thinning performance and creep recovery performance, effectively preventing common problems of lubricants such as volatility and leakage during use. The gel lubricant has great potential in extending the service life of machines and reducing operating energy consumption, and is expected to become a new type of high-performance lubricant. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1Actual photos of the gel lubricants prepared in Application Examples 1 to 3;

[0033] Figure 2 Actual photos of the gel lubricants prepared in Application Examples 4 to 6;

[0034] Figure 3 This is a diagram of the solubility test results. DETAILED DESCRIPTION

[0035] The present invention provides an ionic polymer gel factor, characterized in that it has a structure shown in Formula 1:

[0036]

[0037] In Formula 1, m, n and o are the molar proportions of the corresponding units, wherein m accounts for 10 to 30%, n accounts for 50 to 70%, and o accounts for 10 to 30%; in a specific embodiment, m accounts for 10%, 15%, 20%, 25% or 30%; n accounts for 50%, 55%, 60%, 65% or 70%; o accounts for 10%, 15%, 20%, 25% or 30%.

[0038] In the present invention, X in Formula 1 is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group; the sulfonate group preferably includes The phosphate group preferably includes The benzenesulfonate group preferably includes dodecylbenzenesulfonate group; the phosphite group preferably includes dibutyl phosphite group.

[0039] The ionic polymer gel factor provided by the present invention has good solubility in base lubricants such as mineral base oil and synthetic base oil; in addition, the ionic polymer gel factor contains N, O, S and P heteroatoms, which form a strong adsorption layer with the metal surface through their polar parts, provide good lubricity and reduce direct contact with the metal surface, and undergo tribochemical reaction with the metal surface during friction to generate a tribochemical reaction film to protect the metal from mechanical wear and chemical corrosion.

[0040] The present invention provides a method for preparing the ionic polymer gel factor described in the above scheme, comprising the following steps:

[0041] Mixing raw monomers, polar organic solvents and initiators to carry out free radical polymerization to obtain the ionic polymer gel factor;

[0042] The raw material monomers include urea monomers, octadecyl methacrylate monomers and ionic monomers, and the molar proportions of the urea monomers, octadecyl methacrylate monomers and ionic monomers in the raw material monomers correspond to the proportions of m, n and o in the gel factor of the ionic polymer respectively;

[0043] The structure of the urea monomer is shown in Formula 2, and the structure of the ionic monomer is shown in Formula 3:

[0044]

[0045] In formula 3, X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

[0046] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.

[0047] The urea-based monomer will first be described below.

[0048] In the present invention, the urea monomer is preferably prepared by an addition reaction between isocyanoethyl methacrylate and octadecylamine.

[0049] The method for preparing the urea-based monomer preferably comprises the following steps: mixing octadecylamine, a polar organic solvent and isocyanoethyl methacrylate, and performing an addition reaction under stirring conditions to obtain the urea-based monomer.

[0050] In the present invention, the mixing preferably comprises: dissolving octadecylamine in a polar organic solvent, and then dropping isocyanoethyl methacrylate into the resulting solution.

[0051] In the present invention, the molar ratio of isocyanoethyl methacrylate to octadecylamine is preferably 1:(0.9-1.2). In a specific embodiment, the molar ratio of isocyanoethyl methacrylate to octadecylamine can be 1:0.9, 1:1, 1:1.1 or 1:1.2.

[0052] In the present invention, the polar organic solvent preferably includes dichloromethane or acetonitrile; the volume ratio of the total molar amount of octadecylamine and isocyanoethyl methacrylate to the polar organic solvent is preferably 0.1 mol: (100-150) mL, and in specific embodiments, it can be 0.1 mol: 100 mL, 0.1 mol: 110 mL, 0.1 mol: 120 mL, 0.1 mol: 130 mL, 0.1 mol: 140 mL or 0.1 mol: 150 mL.

[0053] In the present invention, the temperature of the addition reaction is preferably -20 to 60°C, and the time of the addition reaction is preferably 3 to 6 hours; in a specific embodiment, the temperature of the addition reaction can be -20°C, -10°C, 0°C, 10°C, 20°C, 25°C, 30°C, 40°C, 50°C or 60°C, and the time of the addition reaction can be 3h, 4h, 5h or 6h.

[0054] In the addition reaction process of the present invention, the isocyanate (-N=C=O) in isocyanoethyl methacrylate undergoes a nucleophilic addition reaction with the amino group (-NH2) in octadecylamine to generate a urea monomer, and the reaction equation is as follows:

[0055]

[0056] In the present invention, as the addition reaction proceeds, urea monomers are continuously precipitated. In the present invention, the obtained product is preferably washed with ethyl acetate three times, the solvent is removed by suction filtration, and vacuum dried at 35° C. overnight to obtain urea monomers.

[0057] Next, the ionic monomer will be described.

[0058] In the present invention, when the ionic monomer is MDS (structure shown in Formula 4),

[0059]

[0060] The MDS is preferably prepared by ion exchange reaction of methacryloyloxyethyl trimethyl ammonium chloride and sodium dodecyl sulfate; specifically, the preparation method of the MDS preferably includes the following steps: mixing methacryloyloxyethyl trimethyl ammonium chloride, sodium dodecyl sulfate and water, and performing ion exchange reaction under stirring and light-shielding conditions to obtain the MDS.

[0061] In the present invention, the molar ratio of the methacryloyloxyethyl trimethyl ammonium chloride and sodium dodecyl sulfonate is preferably 1: (0.8-1.5). In a specific embodiment, the molar ratio of the methacryloyloxyethyl trimethyl ammonium chloride and sodium dodecyl sulfonate can be 1: 0.8, 1: 0.9, 1: 1, 1: 1.1, 1: 1.2, 1: 1.3 or 1: 1.5. In the present invention, the volume ratio of the total molar amount of the methacryloyloxyethyl trimethyl ammonium chloride and sodium dodecyl sulfonate to water is preferably 0.1 mol: (100-150) mL. In a specific embodiment, it can be 0.1 mol: 100 mL, 0.1 mol: 110 mL, 0.1 mol: 120 mL, 0.1 mol: 130 mL, 0.1 mol: 140 mL or 0.1 mol: 150 mL.

[0062] In the present invention, the water is preferably deionized water; the temperature of the ion exchange reaction is preferably 25-80°C, and the time is preferably 8-48h; in a specific embodiment, the temperature of the ion exchange reaction can be 25°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, and the time of the ion exchange reaction can be 8h, 10h, 15h, 20h, 25h, 30h, 36h, 40h or 48h.

[0063] In the present invention, after the ion exchange reaction, the product system is preferably cooled to room temperature, dialyzed in deionized water for 48 to 96 hours, and freeze-dried in a vacuum to obtain MDS. In the present invention, the relative molecular weight of the dialysis membrane used for the dialysis is preferably 400. The present invention purifies MDS by dialysis to avoid damage to the structure of MDS by high temperature or severe physical treatment.

[0064] In the present invention, the reaction equation for preparing MDS using methacryloyloxyethyl trimethylammonium chloride and sodium dodecyl sulfate is as follows:

[0065]

[0066] In the present invention, when the ionic monomer is MDEHP (structure shown in Formula 5),

[0067]

[0068] The MDEHP is preferably prepared by ion exchange reaction between methacryloyloxyethyl trimethyl ammonium chloride and di(2-ethylhexyl) sodium phosphate. The preparation method of MDEHP is the same as that of MDS, except that sodium dodecyl sulfate is replaced by di(2-ethylhexyl) sodium phosphate.

[0069] In the present invention, the reaction equation for preparing MDEHP using methacryloyloxyethyl trimethyl ammonium chloride and di(2-ethylhexyl) sodium phosphate is as follows:

[0070]

[0071] In the present invention, the di(2-ethylhexyl) sodium phosphate is preferably prepared by a method well known in the art. In a specific embodiment, the preparation method of the di(2-ethylhexyl) sodium phosphate preferably comprises the following steps: mixing a di(2-ethylhexyl) phosphate ester and an alcohol solvent, adding a sodium hydroxide aqueous solution dropwise to the resulting mixture until the pH value of the mixture reaches neutral, and removing the alcohol solvent under vacuum to obtain the di(2-ethylhexyl) sodium phosphate.

[0072] In the present invention, the alcohol solvent preferably includes one or more of methanol, ethanol and isopropanol; the present invention does not make special requirements on the amount of the alcohol solvent, as long as the acid-base neutralization reaction can be carried out smoothly. The present invention has no special requirements on the concentration of the sodium hydroxide aqueous solution. In a specific embodiment, the mass concentration of the sodium hydroxide aqueous solution is 20wt.%. After the sodium hydroxide aqueous solution is added to the present invention, the acidic group of the bis(2-ethylhexyl) phosphate is neutralized by sodium hydroxide to generate the corresponding sodium di(2-ethylhexyl) phosphate.

[0073] The preparation method of the ionic polymer gel factor is described below.

[0074] The preparation method of the ionic polymer gel factor comprises the following steps:

[0075] Mixing raw monomers, polar organic solvents and initiators to carry out free radical polymerization to obtain the ionic polymer gel factor;

[0076] The raw material monomers include urea monomers, octadecyl methacrylate monomers and ionic monomers, and the molar proportions of the urea monomers, octadecyl methacrylate monomers and ionic monomers in the raw material monomers correspond to the proportions of m, n and o in the gel factor of the ionic polymer respectively.

[0077] In the present invention, the polar organic solvent preferably includes N,N dimethylformamide (DMF), dimethyl sulfoxide or acetonitrile; the present invention has no special requirements for the amount of the polar organic solvent, as long as it can ensure the free radical polymerization reaction to proceed smoothly. In the present invention, the initiator is preferably an azo initiator, more preferably azobisisobutyronitrile (AIBN); the mass of the initiator is preferably 0.5-2% of the mass of the raw monomer, and in specific embodiments, it can be 0.5%, 0.7%, 1%, 1.5%, 1.8% or 2.0%.

[0078] In the present invention, the initiator is preferably added in batches, more preferably in two batches. When added in two batches, the present invention preferably adds 1 / 2 to 2 / 3 of the initiator at the beginning of the reaction, and then adds the remaining initiator after the reaction has been allowed to react for 1 to 2 hours.

[0079] In the present invention, the temperature of the free radical polymerization reaction is preferably 40 to 120°C, and the time is preferably 4 to 12 hours; in a specific embodiment, the temperature of the free radical polymerization reaction can be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the time of the free radical polymerization reaction can be 4 hours, 6 hours, 8 hours, 10 hours or 12 hours. In the present invention, the free radical polymerization reaction is preferably carried out under nitrogen protection and reflux conditions.

[0080] After the free radical polymerization reaction is completed, the present invention preferably pours the obtained reaction mixture into ethanol to precipitate the product, washes the product with anhydrous ethanol, and dries it at room temperature under vacuum conditions overnight to obtain the ionic polymer gel factor.

[0081] The present invention provides the use of the ionic polymer gel factor described in the above scheme or the ionic polymer gel factor prepared by the preparation method described in the above scheme as a lubricating oil additive.

[0082] The invention provides a gel lubricant, comprising a base lubricating oil and the above-mentioned ionic polymer gel factor.

[0083] The present invention has no special requirements for the base lubricating oil, which can be a mineral base oil or a synthetic base oil. Specifically, base oil A51, base oil NP451, base oil PAO2, base oil PAO10, base oil PAO40, base oil 150N, base oil 150SN, base oil 150BS, base oil Yubase6, base oil 500N, and base oil 500SN are all applicable to the present invention.

[0084] In the present invention, the content of the ionic polymer gel factor in the gel lubricant is preferably 1 to 15 wt.%, and in specific embodiments, it can be 1 wt.%, 3 wt.%, 5 wt.%, 7 wt.%, 9 wt.%, 11 wt.%, 13 wt.% or 15 wt.%.

[0085] The ionic polymer gel factor provided by the present invention has good solubility in base lubricants such as mineral base oil and synthetic base oil; in addition, the ionic polymer gel factor contains N, O, S and P heteroatoms, which form a strong adsorption layer with the metal surface through their polar parts, provide good lubricity and reduce direct contact with the metal surface, and undergo tribochemical reaction with the metal surface during friction to generate a tribochemical reaction film to protect the metal from mechanical wear and chemical corrosion.

[0086] The present invention has no special requirements for the preparation of the gel lubricant. The ionic polymer gel factor is directly dissolved in the base oil under heating conditions, and the gel lubricant can be obtained after cooling.

[0087] The ionic polymer gel factor and its preparation method and application, and the gel lubricant provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0088] The preparation process of the monomers used in the following examples and comparative examples is as follows:

[0089] Preparation of MDEHP: 32.242g (0.1mol) of bis(2-ethylhexyl) phosphate was added to a 500mL round-bottom flask, and 250mL of anhydrous ethanol was added as a solvent. Then, a 20wt.% NaOH aqueous solution was added dropwise to a solution consisting of bis(2-ethylhexyl) phosphate and anhydrous ethanol until the pH value of the mixture reached neutrality, and then the solvent was removed under vacuum to obtain the desired sodium di(2-ethylhexyl) phosphate. A mixture of 34.441g (0.1mol) of sodium di(2-ethylhexyl) phosphate and 22.8468g (0.11mol) of methacrylic acid acyloxyethyl trimethylammonium chloride was dissolved in 270mL of deionized water. The reaction was carried out at room temperature in the dark for 24h, and after the reaction was completed, it was dialyzed in deionized water for 48h. After freeze-vacuum drying, a pure MDEHP ionic liquid was obtained with a yield of 85.72%.

[0090] The structural formula of MDEHP is shown in Formula 5:

[0091]

[0092] Preparation of MDS: A mixture of 28.8379 g (0.1 mol) of sodium dodecyl sulfate and 22.8468 g (0.11 mol) of methacryloyloxyethyl trimethyl ammonium chloride was dissolved in 270 mL of deionized water. The mixture was reacted at room temperature in the dark for 24 h. After the reaction, the mixture was dialyzed in deionized water for 48-96 h. After freeze-drying in a vacuum, pure MDS ionic liquid was obtained with a yield of 76.41%.

[0093] The structural formula of MDS is shown in Formula 4:

[0094]

[0095] Preparation of urea monomer UMA: 29.647 g (0.11 mol) of octadecylamine was dissolved in 250 mL of dichloromethane, and 15.515 g (0.1 mol) of isocyanoethyl methacrylate was added dropwise to the solution at 0°C. The mixture was stirred at 0°C for 3 h, and UMA was continuously precipitated as the reaction continued. The product was washed with ethyl acetate 3 times and vacuum dried at 35°C overnight to obtain a white solid product with a yield of 78.80%.

[0096] The structural formula of UMA is shown in Formula 2:

[0097]

[0098] Example 1

[0099] Preparation of ionic polymer gel factor PMDEHP-PUMA-PSMA: 9.593g (20mmol) MDEHP, 8.493g (20mmol) UMA and 21.161g (60mmol) octadecyl methacrylate (SMA) were dissolved in 62mL DMF solution. The reaction mixture was heated to reflux at 80°C, the total reaction time was 8h, and the reaction was carried out under N2 atmosphere. At the beginning of the reaction, 1wt.% AIBN of the total monomer amount was added as an initiator, and then 0.5wt.% AIBN was added after 1.5h. After the reaction was completed, the reaction mixture was poured into ethanol to precipitate the desired product. The product was washed 3 times with anhydrous ethanol, filtered to remove the solvent, and dried overnight at room temperature in a vacuum oven to obtain the ionic polymer gel factor PMDEHP-PUMA-PSMA with a yield of 88.17%.

[0100] Example 2

[0101] Preparation of ionic polymer gel factor PMDS-PUMA-PSMA: 8.152g (20mmol) MDS, 8.493g (20mmol) UMA and 21.161g (60mmol) SMA were dissolved in 62mL DMF solution. The reaction mixture was heated to reflux at 80°C, the total reaction time was 8h, and the reaction was carried out under N2 atmosphere. At the beginning of the reaction, 1wt.% AIBN of the total monomer amount was added as an initiator, and then 0.5wt.% AIBN was added after 1.5h. After the reaction was completed, the reaction mixture was poured into ethanol to precipitate the desired product. The product was washed 3 times with anhydrous ethanol, filtered to remove the solvent, and dried overnight at room temperature in a vacuum oven to obtain an ionic polymer gel factor PMDS-PUMA-PSMA with a yield of 73.62%.

[0102] Application Examples 1 to 3

[0103] Preparation of PMDEHP-PUMA-PSMA gel lubricant: The PMDEHP-PUMA-PSMA gel factor in Example 1 was dissolved in 5 g of 500SN base oil according to 5 wt.%, 10 wt.%, and 15 wt.% of the lubricant, respectively, and heated at 80°C for 30 min to fully dissolve, and then cooled to form Figure 1 PMDEHP-PUMS-PSMA gel lubricant shown.

[0104] Depend on Figure 1 It can be seen that the gel factor is dissolved in the base oil and forms a gel lubricant after cooling, which no longer shows fluidity.

[0105] Application Examples 4 to 6

[0106] Preparation of PMDS-PUMA-PSMA gel lubricant: The PMDS-PUMA-PSMA gel factor in Example 2 was dissolved in 5 g of 500SN base oil according to 5 wt.%, 10 wt.%, and 15 wt.% of the lubricant, respectively, and heated at 80°C for 30 min to fully dissolve, and then cooled to form Figure 2 PMDS-PUMS-PSMA gel lubricant shown.

[0107] Depend on Figure 2 It can be seen that the gel factor is dissolved in the base oil and forms a gel lubricant after cooling, which no longer shows fluidity.

[0108] Performance Test:

[0109] According to the ratio of the mass of the ionic polymer gel factor to the total mass of the base oil of 15%, PMDEHP-PUMA-PSMA prepared in Example 1 and PMDS-PUMA-PSMA prepared in Example 2 were added to the base oil for solubility test. The test conditions were heating and stirring at 80°C for 30 minutes. Two base oils were tested, namely 500SN base oil and PAO10 base oil. The test results are shown in Table 1. Figure 3 . Figure 3 In the figure, a is PMDEHP-PUMA-PSMA dissolved in 500SN, b is PMDEHP-PUMA-PSMA dissolved in PAO10, c is PMDS-PUMA-PSMA dissolved in 500SN, and d is PMDS-PUMA-PSMA dissolved in PAO10. Figure 3 It can be seen that the two polymer gel factors have good solubility in 500SN (mineral base oil) and PAO10 base oil (synthetic base oil).

[0110] The PMDEHP-PUMA-PSMA gel lubricant obtained in Examples 1 to 3 was tested for friction performance, and base oil 500SN was used as a blank control. The SRV-V micro-vibration friction and wear tester produced by Optimol Grease Company of Germany was used for testing. The friction pair contact mode was ball-disk contact. The test conditions were: temperature 25°C, frequency 25Hz, amplitude 1mm, load 300N, test time 30min, the upper test ball was AISI 52100 steel ball (Φ=10mm), and the lower sample was AISI 52100 steel block (hardness 700~750HV); the wear volume of the lower sample was measured by a fully automatic true color confocal microscope DCM8, and the test results are shown in Table 1.

[0111] Table 1 Tribological properties of application examples 1 to 3 and base oil 500SN

[0112] Base oil 500SN 5% gel 10% gel 15% gel Average friction coefficient 0.1835 0.0996 0.1019 0.1011 <![CDATA[Average wear volume (10 -4 mm 3 )]]> 22.3593 2.6688 2.7055 2.6716

[0113] It can be seen from Table 1 that under steel-steel contact, PMDEHP-PUMA-PSMA gel lubricant exhibits excellent tribological properties: in the long-term friction test under a load of 300N, compared with the 500SN base oil, the average friction coefficient (COF) of 15wt.% PMDEHP-PUMA-PSMA gel lubricant was reduced by 44.90%, and the wear was reduced by 88.05%.

[0114] The PMDS-PUMA-PSMA gel lubricant obtained in Examples 4 to 6 was tested for friction performance, and base oil 500SN was used as a blank control. The test conditions were the same as those in Examples 1 to 3, and the test results are shown in Table 2.

[0115] Table 2 Tribological properties of application examples 4 to 6 and base oil 500SN

[0116] Base oil 500SN 5% gel 10% gel 15% gel Average friction coefficient 0.1835 0.1018 0.0988 0.0995 <![CDATA[Average wear volume (10 -4 mm3)]]> 22.3593 3.2321 3.5689 4.5465

[0117] As shown in Table 2, under steel-steel contact, the PMDS-PUMA-PSMA gel lubricant exhibits excellent tribological properties: in the long-term friction test under a load of 300N, the average COF of the 15wt.% PMDEHP-PUMA-PSMA gel lubricant was reduced by 45.78% and the wear was reduced by 79.67% compared with the 500SN base oil.

[0118] Comparative Example 1

[0119] The difference from Example 1 is that MDEHP is omitted and a two-component gel factor PUMA-PSMA is prepared.

[0120] The PUMA-PSMA of Comparative Example 1 was dissolved in 500SN base oil at 5 wt.% of the lubricant, and heated at 80° C. for 30 min to fully dissolve, thereby forming a gel lubricant.

[0121] The friction coefficient of the gel lubricant is similar to that of Application Examples 1 to 6, but the load-bearing capacity is significantly reduced.

[0122] When the addition amount of gel factor is 5wt.%, the failure load of the gel lubricant prepared by the two-component gel factor PUMA-PSMA is 450N, the failure load of PMDEHP-PUMS-PSMA gel lubricant is 850N, and the failure load of PMDS-PUMS-PSMA gel lubricant is 550N.

[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An ionic polymer gel factor, characterized in that: It has the structure shown in formula 1: In Formula 1, m, n and o are the molar proportions of the corresponding units, wherein m accounts for 10 to 30%, n accounts for 50 to 70%, and o accounts for 10 to 30%; X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

2. The ionic polymer gel factor according to claim 1, characterized in that The sulfonate group includes 3. The ionic polymer gelator according to claim 1, characterized in that The phosphate group includes 4. The ionic polymer gelator according to claim 1, characterized in that The m accounts for 20%, the n accounts for 60%, and the o accounts for 20%.

5. The method for preparing the ionic polymer gelator according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing raw monomers, polar organic solvents and initiators to carry out free radical polymerization to obtain the ionic polymer gel factor; The raw material monomers include urea monomers, octadecyl methacrylate monomers and ionic monomers, and the molar proportions of the urea monomers, octadecyl methacrylate monomers and ionic monomers in the raw material monomers correspond to the proportions of m, n and o in the gel factor of the ionic polymer respectively; The structure of the urea monomer is shown in Formula 2, and the structure of the ionic monomer is shown in Formula 3: In formula 3, X is a sulfonate group, a phosphate group, a benzenesulfonate group or a phosphite group.

6. The preparation method according to claim 5, characterized in that: The temperature of the free radical polymerization reaction is 40 to 120° C. and the time is 4 to 12 hours.

7. The preparation method according to claim 5, characterized in that: The mass of the initiator is 0.5-2% of the mass of the raw monomer.

8. Use of the ionic polymer gel factor according to any one of claims 1 to 4 or the ionic polymer gel factor prepared by the preparation method according to any one of claims 5 to 7 as a lubricating oil additive.

9. A gel lubricant, characterized in that: The invention comprises a base lubricating oil and an ionic polymer gel factor; the ionic polymer gel factor is the ionic polymer gel factor according to any one of claims 1 to 3 or the ionic polymer gel factor prepared by the preparation method according to any one of claims 4 to 7.

10. The lubricating jelly according to claim 9, characterized in that: The content of the ionic polymer gel factor in the gel lubricant is 1 to 15 wt.%.

Citation Information

Patent Citations

  • Functionalized polymer coated ionic liquid lubricating oil additive as well as preparation method and application thereof

    CN110655967A

  • Ureido polymer gelator and preparation method thereof, and gel lubricant and preparation method and application thereof

    CN112724312A

  • Functionalized viscosity index improver, preparation method thereof and application of functional viscosity index improver as basic lubricating oil additive

    CN117777351A

  • Method of producing gel containing ionic liquid

    WO2013146745A1